Exploration of MR-guided head and neck hyperthermia by phantom testing of a modified prototype applicator for use with proton resonance frequency shift thermometry. (May 2014) - Numan, Wouter C.M.; Hofstetter, Lorne W.; Kotek, Gyula; Bakker, Jurriaan F.; Fiveland, Eric W.; Houston, Gavin C.; Kudielka, Guido; Yeo, Desmond T.B.; Paulides, Margarethus M.
Abstract Magnetic resonance thermometry (MRT) offers non-invasive temperature imaging and can greatly contribute to the effectiveness of head and neck hyperthermia. We therefore wish to redesign the HYPERcollar head and neck hyperthermia applicator for simultaneous radio frequency (RF) heating and magnetic resonance thermometry. In this work we tested the feasibility of this goal through an exploratory experiment, in which we used a minimally modified applicator prototype to heat a neck model phantom and used an MR scanner to measure its temperature distribution. We identified several distorting factors of our current applicator design and experimental methods to be addressed during development of a fully MR compatible applicator. To allow MR imaging of the electromagnetically shielded inside of the applicator, only the lower half of the HYPERcollar prototype was used. Two of its antennas radiated a microwave signal (150 W, 434 MHz) for 11 min into the phantom, creating a high gradient temperature profile (ΔTmax = 5.35 °C). Thermal distributions were measured sequentially, using drift corrected proton resonance frequency shift-based MRT. Measurement accuracy was assessed using optical probe thermometry and found to be about 0.4 °C (0.1–0.7 °C). Thermal distribution size and shape were verified by thermal simulations and found to have a good correlation (r2 = 0.76).